Analysis of Bikago Usage by the Character Honda Tohru in Anime Fruits Basket Season 1 - Made Gede Bima Putra Jaya Kesuma; Putu Dewi Merlyna Yuda Pramesti; I Kadek Antartika (Universitas Negeri Padang, 2026)
As a form of keigo in the Japanese language, bikago functions to soften utterances without elevating the interlocutor's status and is closely associated with politeness and female gender identity. This study describes the use of bikago by the character Tohru Honda in the anime Fruits Basket Season 1 (episodes 1–10) using a qualitative descriptive approach with the observation and note-taking method. It aims to examine the forms, functions, and underlying factors of bikago usage. Data gathered from Tohru’s dialogue utterances were analyzed using the frameworks of Bunka Shingikai (2007) and Tsujimura (1991). The findings reveal five forms of bikago across 65 identified data points: o-wago, o-kango, go-wago, go-kango, and o-konshugo, with o-wago emerging as the most dominant. Additionally, three distinct functions are identified—softening speech, creating familiarity, and demonstrating elegance— with the speaker predominantly utilizing the feature to deliver softer expressions to her interlocutors. The underlying motivations include relational dynamics, social status, and participant-specific factors, which encompass the specific interlocutor, the speech situation, as well as the speaker’s emotional state and feelings during the interaction.